“When I’m in Pain, Everything Is Overwhelming”: Implications of Pain in Adults With Autism on Their Daily Living and Participation - Kalingel-Levi, Merry; Schreuer, Naomi; Granovsky, Yelena; Bar-Shalita, Tami; Weissman-Fogel, Irit; Hoffman, Tseela; Gal, Eynat (Frontiers in Psychology, 2022)
Pain sensation in autism spectrum disorder (ASD) has been a growing research field in the last two decades. Existing pain research has focused on pain sensitivity, suggesting either hyposensitivity or hypersensitivity to pain in individuals with ASD. However, research about other aspects of pain experience is scarce. Moreover, most pain-related research in ASD focused on quantitative measures, such as neuroimaging or parental reports. Instead, this paper aimed to illuminate the various aspects of pain experience as perceived by adults with ASD. Its descriptive qualitative research design incorporated semi-structured interviews and deductive thematic analysis. This phenomenological approach captured the subjective pain experience through the lens of people with ASD. Four primary themes emerged from the data: (a) physical pain experience, including the sequence of pain sensitivity, pain awareness, pain-related emotional aspects, and pain communication; (b) direct and indirect coping strategies; (c) function and participation outcomes; and (d) suggestions for Healthcare Providers. The findings echo the crucial role of pain awareness and communication in the pain experience of people with ASD. These two factors have been reported as profoundly influencing coping strategies, function, and participation. The results emphasize the need to expand the exploration of pain in this population, calling for greater understanding, and listening to this population’s unique pain profiles and experiences to promote better-suited evaluation, diagnosis, and intervention in pain conditions.